2004
DOI: 10.1242/dev.01535
|View full text |Cite
|
Sign up to set email alerts
|

GDF11 modulates NGN3+ islet progenitor cell number and promotes β-cell differentiation in pancreas development

Abstract: Identification of endogenous signals that regulate expansion and maturation of organ-specific progenitor cells is a major goal in studies of organ development. Here we provide evidence that growth differentiation factor 11(GDF11), a member of the TGF-β ligand family, governs the number and maturation of islet progenitor cells in mouse pancreas development. Gdf11 is expressed in embryonic pancreatic epithelium during formation of islet progenitor cells that express neurogenin 3. Mice deficient for Gdf11 harbor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
138
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(149 citation statements)
references
References 65 publications
(87 reference statements)
9
138
1
1
Order By: Relevance
“…We found that the incidence of cardiac malformation and right pulmonary isomerism was significantly increased in ActRIIB Ϫ/Ϫ Smad2 ϩ/Ϫ mice compared with ActRIIB Ϫ/Ϫ mice. In addition, we demonstrated that hypoplastic islets were found not in only ActRIIB Ϫ/Ϫ but also Smad2 ϩ/Ϫ mice, which was consistent with previous studies (Kim et al, 2000;Harmon et al, 2004). Interestingly, more severe phenotypes were found in the compound heterozygous ActRIIB ϩ/Ϫ Smad2 ϩ/Ϫ mice.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the incidence of cardiac malformation and right pulmonary isomerism was significantly increased in ActRIIB Ϫ/Ϫ Smad2 ϩ/Ϫ mice compared with ActRIIB Ϫ/Ϫ mice. In addition, we demonstrated that hypoplastic islets were found not in only ActRIIB Ϫ/Ϫ but also Smad2 ϩ/Ϫ mice, which was consistent with previous studies (Kim et al, 2000;Harmon et al, 2004). Interestingly, more severe phenotypes were found in the compound heterozygous ActRIIB ϩ/Ϫ Smad2 ϩ/Ϫ mice.…”
Section: Introductionsupporting
confidence: 92%
“…It has been shown that double heterozygous mice for nodal and Smad2 exhibit similar laterality defects seen in ActRIIB Ϫ/Ϫ mice, suggesting that nodal may signal through ActRIIB and Smad2 during thoracic organ patterning (Nomura and Li, 1998). With regard to pancreas islet development, GDF11-deficient mice have been shown to exhibit hypoplasia of the islet, due to the defect in ␤ cell maturation, reminiscent of the phenotype found in Smad2 ϩ/Ϫ mice, suggesting that GDF11 uses Smad2 as a downstream signal transducer (Harmon et al, 2004). We thus speculated that Smad2 acts downstream to ActRIIB in these developmental processes, such as left-right patterning and pancreas development.…”
Section: Introductionmentioning
confidence: 94%
“…Perhaps the most likely candidate is GDF-11͞BMP-11, which is highly related to myostatin in the mature region of the protein (2,23,24) and is also expressed in skeletal muscle. Genetic studies in mice have demonstrated clear roles for Gdf11 in regulating anterior͞posterior patterning (25), kidney development (25,26), neuronal development (27,28), and pancreas development (29). Because mice completely lacking GDF-11͞BMP-11 die during the perinatal period, however, elucidation of the role, if any, that GDF-11͞ BMP-11 plays in regulating muscle growth will require the generation of mice in which the Gdf11 gene can be deleted in either a muscle-specific or inducible manner.…”
Section: Resultsmentioning
confidence: 99%
“…Light images were captured with a Zeiss (Oberkochen, Germany) Axioplan 2 microscope and software. Cell counting, point-counting morphometry, and ␤ cell quantification were performed by using standard morphometric techniques (14,44,45) or as described in SI Materials and Methods. For quantification of immunostained cells, pancreas tissue was obtained from at least four mice per genotype.…”
Section: Methodsmentioning
confidence: 99%